Enhanced Power Conversion Efficiency of P3HT : PC71BM Bulk Heterojunction Polymer Solar Cells by Doping a High-Mobility Small Organic Molecule - Hanyu Wang; Xiao Wang; Pu Fan; Xin Yang; Junsheng Yu (International Journal of Photoenergy)
The effect of molecular doping with TIPS-pentacene on the photovoltaic performance of polymer solar cells (PSCs) with a structure of ITO/ZnO/poly(3-hexylthiophene-2,5-diyl) (P3HT) : [6,6]-phenyl C71-butyric acid methyl ester (PC71BM) : TIPS-pentacene/MoOx/Ag was systematically investigated by adjusting TIPS-pentacene doping ratios ranged from 0.3 to 1.2 wt%. The device with 0.6 wt% TIPS-pentacene exhibited the enhanced short-circuit current and fill factor by 1.23 mA/cm2 and 7.8%, respectively, resulting in a maximum power conversion efficiency of 4.13%, which is one-third higher than that of the undoped one. The photovoltaic performance improvement was mainly due to the balanced charge carrier mobility, enhanced crystallinity, and matched cascade energy level alignment in TIPS-pentacene doped active layer, resulting in the efficient charge separation, transport, and collection.